Situation Report: Hungary, 20 July 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Hungary Signs East Block's First Environmental Agreement with the West / by Eva Lengyel Seventh World Congress of Lutherans to Be Held in Budapest / by Edith Markos No Improvement in the Situation of Romania's Hungarian Minority / by Judith Pataki New Incentives to Increase Convertible Currency Income / by Laszlo Rasko Marta Meszaros's View of the 1950s in Hungary / by Judith Pataki